Numerical modeling of force interaction between slab-pile foundations and soil massif - Gusev, Georgiy Nikolaevich; Tashkinov, Anatoliy Alexandrovich (Computational Continuum Mechanics, 2012)
Displacements of the field of piles arranged in a generally regular grid pattern are represented as deformations of a laminated massive with incomplete coupling system. Using the elastic foundation model with two coefficients of subgrade resistance, the formula for actual load distribution between the slab and piles (SPF) is derived. A series of numerical experiments are carried out to verify the obtained ratio.